Development of FYP online system for outcome based education - Mutholib, Abdul; Gunawan, Teddy Surya; Kartiwi, Mira (2011)
This paper describes the development of Final Year Project (FYP) Online System in order to support the implementation of Outcome Based Education (OBE). OBE has become a model for learning environment and curriculum design for the educational system. OBE sets obvious educational goals and helps the student to achieve those goals. The proposed system is supporting the OBE in order to make a transparent and objective evaluation of each student which is essential to introduce continuous quality improvement (CQI) as mandated by Engineering Accreditation Council (EAC) in Malaysia. Furthermore, the system enables an effective and efficient FYP administration. Contributing to the education and development of open source, the system will be developed under Open Source Initiative including GNU Linux Ubuntu, Apache for the web server, MySQL for the relation database management system (RDBMS), PHP server scripting and jQuery java script framework which is addressed by Google. Moreover, in order to gain the best quality and the limited time as well, we are using Rapid Application Development (RAD) as our software development life cycle. In conclusion, the aim of this paper is to address the development of FYP online system as an efficient and effective way to support the OBE model.